High Salt Intake Increases Blood Pressure in Normal Rats: Putative Role of 20-HETE and No Evidence on Changes in Renal Vascular Reactivity - A. Walkowska; M. Kuczeriszka; J. Sadowski; K.H. Olszyñski; L. Dobrowolski; L. Červenka; B.D. Hammock; E. Kompanowska-Jezierska (Karger Publishers, 2015)
Background/Aims. High salt (HS) intake may elevate blood pressure (BP), also in animals without genetic salt sensitivity. The development of salt-dependent hypertension could be mediated by endogenous vasoactive agents; here we examined the role of vasodilator epoxyeicosatrienoic acids (EETs) and vasoconstrictor 20-hydroxyeicosatetraenoic acid (20-HETE). Methods. In conscious Wistar rats on HS diet systolic BP (SBP) was examined after chronic elevation of EETs using 4-[4-(3-adamantan-1-yl-ureido)-cyclohexyloxy]-benzoic acid (c-AUCB), a blocker of soluble epoxide hydrolase, or after inhibition of 20-HETE with 1-aminobenzotriazole (ABT). Thereafter, in acute experiments the responses of renal artery blood flow (Transonic probe) and renal regional perfusion (laser-Doppler) to intrarenal acetylcholine (ACh) or norepinephrine were determined. Results. HS diet increased urinary 20-HETE excretion. The SBP increase was not reduced by c-AUCB but prevented by ABT until day 5 of HS exposure. Renal vasomotor responses to ACh or norepinephrine were similar on standard and HS diet. ABT but not c-AUCB abolished the responses to ACh. Conclusions. 20-HETE seems to mediate the early-phase HS diet-induced BP increase while EETs are not engaged in the process. Since HS exposure did not alter renal vasodilator responses to Ach, endothelial dysfunction is not a critical factor in the mechanism of salt-induced blood pressure elevation.